MODELS OF CORPORATE MANAGEMENT IN THE TRANSFORMATION MANAGEMENT CONCEPTION - A. E. Suleymankadieva (Дискурс, 2017)
The article examines a new concept of transformation management which is an alternative to the classical theory of management. The concept specific character in comparison with the theory of change management is shown. The author substantiates the historical sequence and interrelationship of the four world models of corporate management (humanistic, holistic, rational and pragmatic) in terms of the key elements and main features of transformational management. Much attention is paid to the analysis of key elements and main functions of transformation management which are associated with strategic renewal through the transformation flows, cross- and transcultural dynamics, transdisciplinary (transfunctional) and transpersonal approaches to corporate management.